Phenomenological insights into the FLASH radiotherapy-induced abscopal effect - Castorina, Paolo; Ferini, Gianluca; Romano, Francesco (Frontiers in Oncology, 2025)
BackgroundThe abscopal effect suggests that the impact of radiotherapy extends beyond the direct tumor local regression, due to activation of the immune response. Its effectiveness may vary depending on whether high- or low-radiation doses are used. In FLASH therapy, the high-dose rate treatment induces systemic effects that may trigger an abscopal response.MethodsWe discuss a phenomenological, computational model, based on available in vivo FLASH radiotherapy data, to quantitatively analyze the possible synergistic effects with the immune system to produce a systemic effect.ResultsThe method enables a quantitative assessment of the interaction between FLASH radiotherapy and the activated immune response, based on observations of metastatic shrinkage due to the FLASH treatment of the primary tumor.